EFFECT OF NATURAL SUCKLING ON POSTPARTUM REPRODUCTIVE PERFORMANCE OF NUBIAN GOATS (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to investigate the effect of natural suckling on reproductive performance of Nubian Goats. The study involved 20 multiparousNubian goats allocated randomly according to body weight and age to two equal groups of 10 does each. Group A suckled their kids for 13 weeks while group B (control) kids were reared artificially by bottle for 13 weeks. The results showed that the mean postpartum anoestrus interval (PPAI) length was 57.8±21.5 days compared to 20.4± 4.4 days in the two groups respectively. The results indicateda high significant difference (P